Correlation of IL-17 Serum Levels with Carotid Intima-Media Thickness and Degree of Disease Activity in Rheumatoid Arthritis Patients at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia - Lingga Gumelar; Hermansyah; Radiyati; Taufik Indrajaya; Zulkhair Ali; Irsan Saleh (HM Publisher, 2022)
Background: Rheumatoid arthritis (AR) is an autoimmune disease characterized by chronic and progressive systemic inflammation, in which the joints are the main target. AR has long been associated with increased cardiovascular risk. Vascular inflammation plays an important role in atherosclerosis. In AR, there is an increase in IL-17, which accelerate the formation of atherosclerosis. In Indonesia alone, there is no data that publishes the correlation between IL-17 levels with carotid IMT and the severity of AR. Methods: This type of research is a descriptive observational study with a correlation test approach. A total of 31 subjects participated in this study who were AR patients and calculated a DAS score of 28. Carotid IMT was measured by high-resolution carotid Doppler ultrasound B-mode ultrasound machine (PHILIPS, iE33) equipped with an 11 MHz linear array transducer. IL-17 was measured by the ELISA method. Data analysis was performed with a correlation test with SPSS software version 25. Results: There was a strong positive correlation between IL-17 and the degree of disease activity in AR (DAS28 score) with r = 0.657; p = 0.0001; n=31. There was no significant correlation between carotid IMT and IL-17 levels (r= 0,207; p=0,264; n=31). Conclusion: There is a strong positive correlation between IL-17 and the degree of AR disease activity. There was no significant correlation between carotid IMT and IL-17 levels.